2009
DOI: 10.3171/2009.3.peds08308
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of ventriculoperitoneal shunt placement in Grade IV tubercular meningitis with hydrocephalus: a retrospective analysis in 95 patients

Abstract: Object Hydrocephalus is the most common complication of tubercular meningitis (TBM). Relieving hydrocephalus by ventriculoperitoneal (VP) shunt placement has been considered beneficial in patients in Palur Grade II or III. The role of VP shunt placement in those of Grade IV is controversial and the general tendency is to avoid its use. Some authors have suggested that patients in Grade IV should receive a shunt only if their condition improves with a trial placement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 11 publications
2
20
1
Order By: Relevance
“…Historically, surgical intervention was only recommended with grade 2 or 3 TBM hydrocephalus (normal or mildly altered sensorium; easily arousable) due to increased mortality and risk of poor surgical outcome in patients with grade 4 disease (deeply comatose). However, a retrospective analysis of 95 patients with grade 4-associated hydrocephalus who underwent shunt placement demonstrated favorable outcomes in 33%–45% of patients, suggesting that there may be a role for surgical intervention even in advanced TBM hydrocephalus [70]. In this study, poor neurological outcomes after shunt placement were associated with age < three years and > three days in duration of symptoms.…”
Section: Treatmentmentioning
confidence: 67%
“…Historically, surgical intervention was only recommended with grade 2 or 3 TBM hydrocephalus (normal or mildly altered sensorium; easily arousable) due to increased mortality and risk of poor surgical outcome in patients with grade 4 disease (deeply comatose). However, a retrospective analysis of 95 patients with grade 4-associated hydrocephalus who underwent shunt placement demonstrated favorable outcomes in 33%–45% of patients, suggesting that there may be a role for surgical intervention even in advanced TBM hydrocephalus [70]. In this study, poor neurological outcomes after shunt placement were associated with age < three years and > three days in duration of symptoms.…”
Section: Treatmentmentioning
confidence: 67%
“…14,20 There is recent literature supporting the role of CSF diversion even in patients in Grade IV TBM. 22 However, literature evaluating the role of CSF diversion in HIV-positive patients with TBM and hydrocephalus is scarce. Nadvi et al reported a series of 30 patients with TBM and hydrocephalus, of whom 15 were HIV positive.…”
mentioning
confidence: 99%
“…This is in accordance with a previous study from our institution, which demonstrated significant improvement following shunt surgery even in poor grade patients. [8] Shunt malfunction was diagnosed by clinical examination, computed tomography (CT) scan of the head and shunt tap whenever deemed necessary. Only patients with shunt malfunction due to shunt tube block was included in the study, whereas those with improper shunt position (ventricular catheter malposition and distal tube malposition) and shunt infection were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%